Estudo sobre a implementação do curso de mestrado na Escola de Direito do Rio de Janeiro da Fundação Getulio Vargas - Ribeiro, Margareth Jacobi (2012)
This dissertation proposes to examine the central issues related to the elaboration and implementation of an academic (stricto sensu) master program. The opening of an academic master program in Law by FGV DIREITO RIO, focus on Regulatory Law, represents a trademark in innovation and pioneering, since it will be the first program as such to be offered in Brazil. Moreover, it will assist in meeting demand for training of researchers in the State of Rio de Janeiro, which currently has only nine academic (stricto sensu) master programs accredited by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (Capes). The team responsible for drafting the proposal conducted a research on the nine academic master program available, as well as a detailed examination on the basic premises and required features necessary to submit a formal proposal for the opening of a new academic master program respecting the norms and procedures established by the Capes. The preparation of FGV DIREITO RIO`s academic master program proposal was only possible by adjusting it to the policies of its research centers which confirms the preparation of high-level researchers able to associate solid scientific basis to collaborate in the solution of national and global issues. Thus, to achieve these goals, it was also essential to gather efforts from all research centers to provide FGV DIREITO RIO with their expertise and knowledge resulted from their scientific projects under development.